3D printed heterogeneous cation exchange membrane processed using stereolithography - Zarybnicka, Lucie; Meloun, Zbysek; Safka, Jiri; Truxova, Veronika; Dvorak, Karel; Machotová, Jana (Wiley-Blackwell, 2023)
Membrane chemistry belongs to the field in which 3D printing can advantageously also be used because of enabling the production of prototypes with precisely defined dimensions. The presented work aimed to develop new polymeric compositions for heterogeneous cation exchange membranes manufactured using stereolithography (SLA) from commercially available materials. Three types of photo-curable thermoset resins (acrylic resin and two types of epoxy resins) were used as polymer matrixes in combination with strong acid cation exchange resin (CER) powder. The membrane production consisted of several stages, namely mixing the photo-curable resin with finely ground CER powder, processing using SLA, and appropriate post-curing using UV light and elevated temperature. The work aimed to monitor the influence of the photocurable resin type and post-curing on the microstructural, electrochemical, and mechanical properties of resulting membrane objects. The results revealed that heterogeneous cation exchange membranes could be processed using SLA from the mixture of the acrylic photo-curable resin and CER powder (weight ratio of 60/40) without the need for post-curing. These products exhibited high permselectivity (93%), high ion exchange capacity (2.23 meq.g(-1)), and sufficiently low electrical resistance (2200 Omega.cm), which predetermines them for efficient electrophoretic separation.
3D tištěná heterogenní katexová membrána připravená pomocí stereolitografie
Keywords: 3D printing; electrochemical properties; electrophoretic separation; heterogeneous cation exchange membrane; stereolithography; thermoset photopolymer resin; 3D tisk; elektrochemické vlastnosti; elektroforetická separace; heterogenní katexová membrána; stereolitografie; termosetová fotopolymerní pryskyřice